2020
DOI: 10.1177/0363546520971757
|View full text |Cite
|
Sign up to set email alerts
|

Pain Control After Shoulder Arthroscopy: A Systematic Review of Randomized Controlled Trials With a Network Meta-analysis

Abstract: Background: Shoulder arthroscopy is one of the most commonly performed orthopaedic procedures used to treat a variety of conditions, with >500,000 procedures performed each year. Purpose: To systematically review the randomized controlled trials (RCTs) on pain control after shoulder arthroscopy in the acute postoperative setting and to ascertain the best available evidence in managing pain after shoulder arthroscopy to optimize patient outcomes. Study Design: Systematic review and meta-analysis. Methods: A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 103 publications
(42 reference statements)
0
14
0
Order By: Relevance
“…17 A more recent systematic review showed similar results. 18 Chen et al noted the reduced demand for PCA analgesics and decreased opioid-induced adverse events following shoulder surgery when ISB was performed. 19 However, despite a lower incidence of severe pain, a longer time to first analgesic request, and better functionality as measured by the QuickDASH scores at 1 week and 1 month follow-up in those patients who received ISB as compared to those who did not, ISB was not found to be an independent predictor of improved functionality at 1 week and 1 month follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…17 A more recent systematic review showed similar results. 18 Chen et al noted the reduced demand for PCA analgesics and decreased opioid-induced adverse events following shoulder surgery when ISB was performed. 19 However, despite a lower incidence of severe pain, a longer time to first analgesic request, and better functionality as measured by the QuickDASH scores at 1 week and 1 month follow-up in those patients who received ISB as compared to those who did not, ISB was not found to be an independent predictor of improved functionality at 1 week and 1 month follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Four systematic reviews have evaluated randomized controlled trials (RCTs) within knee, 14 hip, 15 and shoulder 16,17 arthroscopy. Warrender et al 17 suggests that the interscalene nerve block is the most effective analgesic for arthroscopic shoulder surgery, while Hurley et al 16 recommend nerve block adjuncts to improve pain control.…”
Section: Introductionmentioning
confidence: 99%
“…Four systematic reviews have evaluated randomized controlled trials (RCTs) within knee, 14 hip, 15 and shoulder 16,17 arthroscopy. Warrender et al 17 suggests that the interscalene nerve block is the most effective analgesic for arthroscopic shoulder surgery, while Hurley et al 16 recommend nerve block adjuncts to improve pain control. In hip arthroscopy, Kunze et al 15 similarly recommend adjunct analgesia, and they suggest that local infiltration analgesia may optimize postoperative pain and opioid consumption.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations